Social Cataloguing Sites: Features and Comparison in Relation to ISBD - Sarkar, Arindam; Bhattachrya, Udayan (Journal of Information and Knowledge, 2019)
In the past few years, the number of social site related applications has increased; and also, these are playing an important role in the collection and sharing of knowledge. These types of application give users the freedom to create vocabulary, which helps to describe and categorize online resources. The social cataloguing applications are a type of web application that helps users to catalogue various items. These social cataloguing sites help users to catalogue their personal book collections, and make the collection known to all users with similar tastes. This study analyzed and evaluated the bibliographic and social features of some selected popular social cataloguing sites and also compared with the data elements prescribed in the International Standard Bibliographic Description (ISBD).